Factors Affecting Small and Medium Business Enterprises in Accessing Loan Facility in Kenya (A Case Study of Embu County) - Itumo, Janet Nthenya (University of Embu, 2019)
This study seeks to identify factors affecting small and medium enterprises in accessing loan facility in Kenya. A case study of Ernbu County. Markets need of this study arise from the fact that a lot of businesses do not expand their business operations and new start-ups are limited due to lack of credit from credit markets. The study explored the factors that are affecting small and medium enterprises when they want to access credit from banks in Embu County. Therefore it aimed at exploring the factors that can help loan seekers to get loans as they want .The main objectives of the study were to establish how collateral, credit worthiness, lending policies, and capital affect accessibility to loans to growth of SME, to find out the impact of credit to the growth of the economy of Embu County.The researcher used descriptive design that provided a link between the theoretical perspectives, research purposes and the data collected which in turn brought out the research findings .The sample was drawn using random sampling technique. Data was collected using semi-structured questionnaires that the researcher pre-tested the research instruments before she began with the study, hence this assisted in the validity of the questionnaire and elimination of misunderstanding of the questions that were asked by the researcher. Data analysis used both qualitative and quantitative in terms of research quantity and identified relevant causes of action. Data was analyzed using descriptive statistics collection which was by use of questionnaires. This was made up of both structured and unstructured questions which helped to avoid being too rigid and to quantify the data especially where structured items were used. This method assisted the researcher to collect accountable information which would not be possible while using interview and observation method due to the personnel's suspicious attitude. From the study that was carried out by the researcher it can be recommended that the banks should be ready to listen to the problems of the loan seekers because most of them will not borrow loans due to one reason or the other. In addition, the government should be on the look when it comes to such matters like interest rates it should regulate the banks to charge a certain fee when small and medium.